Performance of Lucerne (Medicago sativa L.) Under semi-arid Environment. I: Effects of irrigation regime and irrigation system on fodder yield of Lucerne (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted during January to August2007, 2008 and 2009 in the Demonstration Farm of the Faculty ofAgriculture, University of Khartoum lat. 15°40 ́N. Long. 32° 32- and 380m asl. The objectives of the experiment were to study the effect ofirrigation intervals of 8 (W 1 ) and 12 (W 2 ) days both of which received 8mm/day and 96 mm/day respectively. In addition the efficiency ofsprinkler and drip irrigation in production of lucerne fodder under the twoirrigation intervals was evaluated. The stability or variability of fodderyield from monthly cuts with seasonal weather changes was also studied.The results of the experiment showed that the irrigation interval (W 1 )consistently produced higher yield/cut in the three years. Drip irrigationproduced higher fodder yield than the sprinkler during the experimentalperiod at both the irrigation intervals. The yield of fodder was higherduring the cool months of January and February and declined during thehot months of March, April and May. Further decline in fodder yieldresulted during the monsoon months of June, July and August.
Keywords: Lucerne; sprinkler and drip irrigation; water regime; seasonal weather